Exploring the Extent and Depth of Clinical Education on Sepsis SEP-1 Core Measure and the Reported Impact on Outcomes and Compliance rate: A Scoping Review - Alexis J. Wells, MSN; Alysha Sapp, MLIS; Danielle K. Walker, PhD; Kathy A. Baker, PhD (Critical Care Explorations)
OBJECTIVES:. This scoping review aimed to understand the extent and depth of education provided on the severe sepsis and septic shock management bundle quality measure (SEP-1) to frontline clinicians to elicit insight regarding the impact on patient outcomes, the compliance rate, and any efforts to alleviate concerns about clinical judgment challenges with SEP-1. DATA SOURCES:. Seven databases were used: ProQuest, EBSCO Host, Embase, Web of Science, PubMed, MEDLINE, and CINAHL for studies published in 2015 and later using key terms related to sepsis and SEP-1 quality measure. STUDY SELECTION:. Two independent reviewers selected studies that mentioned the Centers for Medicare and Medicaid Services SEP-1 and included education to frontline clinicians on the quality measure as one of the interventions. DATA EXTRACTION:. Data extraction included study design, publication type, what was educated to frontline clinicians, Bennet and Bennet’s “depth of knowledge” through education provided, and any mention of patient outcomes and change in SEP-1 compliance rate from the study. DATA SYNTHESIS:. The initial search yielded 493 articles. After screening for eligibility criteria, 20 studies were ultimately included. When evaluating what details of SEP-1 are being educated, 95% (19/20) of the studies focused on how to identify sepsis as well as the bundle elements required to pass the measure (19/20); however, the deeper details of the measure that allow clinical judgment and still pass the measure are severely lacking. CONCLUSIONS:. Multiple education opportunities not currently addressed in the literature may lead to improvement of the national SEP-1 compliance rate and alleviate clinician concern that the quality measure does not allow for clinical judgment. Without deeper education, this knowledge gap could be a key factor in why the quality measure national compliance rate has halted, raising calls to retire the measure prematurely.